Respon Tanaman Pegagan (Centella asiatica L. Urban) Terhadap Pemberian Pupuk Alami di Bawah Naungan - Neni Musyarofah; Slamet Susanto; Sandra A. Aziz; Suyanto Kartosoewarno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
The objectives of this experiment was to study the growth, yield and qualitative bioactive compounds of Indian pennyworth (Centella asiatica L. Urban) under different shading levels and biofertilizers.  Field experiment was conducted from February until May 2006 at Kuntum Nurseries Bogor.  Split plot design was used in this experiment.  The main plot was shading level: 55, 65 and 75%. The sub plot was biofertilizer types: Fertifort Super, Fertifort Fine and NPK Novelgro fertilizer.  The result of this experiment showed that plants under the 65% shading level significantly showed better growth, biomass weight and qualitative bioactive compounds (tanin, flavonoid, steroid and triterpenoid) than those of 75% shading level.  The 75% shading level was unsuitable because all plants were dead at 10 weeks after fertilizer application; the 55% shading level gave the best growth responses but 55 and 65% shading level gave no significant differences in biomass weight. Biofertilizer gave no significant differences in leaf and stolon numbers, biomass weight and physiological characteristics except NPK content in plant tissue. Significant difference occured only in N plant tissue content because of interaction with shading level. The different effect in qualitative bioactive compound showed that saponin was found in 55% shading level but not in 65% shading level.   Key words:  Shading, biofertilizer, qualitative bioactive compound, Centella asiatica.